The Nymphaion expedition of the State Hermitage Museum (2006–2013) - Sokolova, Olga (Hyperboreus, 2015)
A survey of the excavations at Nymphaion (Kerch) conducted by the expedition of the State Hermitage Museum in 2006–2013.